Frattini theory for N-Lie algebras - Michael Peretzian Williams (Algebra and Discrete Mathematics, 2009)
We develop a Frattini Theory for n-Lie algebras by extending theorems of Barnes' to the n-Lie algebra setting. Specifically, we show some sufficient conditions for the Frattini subalgebra to be an ideal and find an example where the Frattini subalgebra fails to be an ideal.